Effect of allogeneic pure platelet-rich plasma, sodium cloxacillin, and their combination for the treatment of subclinical mastitis in crossbred cows - López, Catalina; Duque-Madrid, Paulo Cesar; Ceballos-Márquez, Alejandro; Carmona, Jorge U. (Frontiers in Veterinary Science, 2024)
Bovine subclinical mastitis (SCM) caused by Gram-positive bacteria is a major cause of economic loss in the dairy industry, exacerbated in situations where antimicrobial resistance is present. Pure platelet-rich plasma (P-PRP) may be a therapeutic alternative for SCM, when used alone or with antibiotics, such as sodium cloxacillin (SC). This study aimed 1) to evaluate the therapeutic efficacy of allogeneic P-PRP, SC, and their combination (P-PRP+SC) in cows with SCM caused by Staphylococcus aureus and by streptococci (S. uberis and S. dysgalactiae); 2) to determine the concentrations of somatic cells (SCC), interleukin 1 beta (IL-1b), tumor necrosis factor-alpha (TNF-a) and TGF-b1 in milk samples of the cows. 130 cows from 4 dairy herds completed the study, of which 40 cows were treated with P-PRP (10 mL), 28 cows with SC (5g), 36 with P-PRP+SC (10mL/5g), and 26 did not receive no treatment (negative control group, NCG). The overall bacteriological cure was observed in 10/40 (25%) cows in the P-PRP group, 9/28 (32.14%) animals in the SC group, 26/36 (72.22%) cows in the P-PRP+SC group, and 10/26 (38.46%) animals in the NCG. SCM caused by S. aureus (82/130, 63.08%), was cured in 6/24 (25%) cows treated with P-PRP, 7/24 (29.2%) cows treated with SC, 8/16 (50%) animals treated with P-PRP+SC, and in 8/18 (44.4%) cows in NCG. For SCM caused by the streptococci (48/130, 36.91%), the cure was achieved in 4/12 (33.3%) cows treated with P-PRP, 2/4 (50%) cows treated with SC, 18/20 (90%) cows treated with P-PRP+SC, and in 2/8 (25%) cows of the NCG. SCC was significantly (P< 0.001) affected by the treatment, herd, cure, bacteria group, and number of calvings factors. IL-1b milk concentrations were significantly (P< 0.001) influenced by treatment and farm factors, and the interaction between these factors. TNF-a milk concentrations were significantly (P< 0.001) influenced by time factor. TGF-b1 milk concentrations were significantly affected by the time and cure factors. The combination of P-PRP and SC showed the best therapeutic response (90%) against bovine SCM caused by streptococci. However, none of the treatments showed an effective therapeutic response against S. aureus.